HUBUNGAN ANTARA MOTIVASI, KETERIKATAN SERTA PILIHAN UNTUK LEBIH PRODUKTIF DALAM MEMPERSIAPKAN PENILAIAN PADA PEMBELAJARAN AKUNTANSI DI LINGKUNGAN BELAJAR VIRTUAL - David Firna Setiawan (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2021)
Changes in conventional learning environments to virtual learning environments have an impact on changes in observation methods of student engagement and participation in accounting classes. This condition can have an impact on reducing their engagement and productivity in learning due to the dominance of external motivation. One strategy that can be used to increase engagement and productivity is the integration of assessment tools such as Quizizz. This study aims to explain the description of the internal motivation, persistence and persistence of students in preparing the assessment. This study also aims to look at the relationship between pleasure, challenge, clinging and persistence in making choices to be more productive and trying to construct these behaviors. The study was conducted on second semester students enrolled in cost accounting classes. The research method was carried out using the one-shot case study. The results showed. Integrating Quizizz in cost accounting lessons can foster internal motivation through the fun and challenges of using the application. Giving regular assignments and feedback can increase student engagement in learning even though it does not occur in the interaction process. Persistence is linearly and significantly related to the choice to be more productive in preparing for the assessment. However, persistence turned out to be not good enough to predict and explain options to be more productive in preparing assessments.Keywords: Motivation, Student Engagement, Productivity,Virtual learning environment